Perbedaan Keterampilan Generik Sains Antara Model Pembelajaran Berbasis Masalah Dengan Inkuiri Terbimbing Ditinjau Dari Kemampuan Berpikir Kritis Siswa SMA - Susilawani Susilawani; Aris Doyan; Syahrial Ayub (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2019)
This study aims:1) To determine the differences in generic science skills of high school students in the problem-based learning model and guided inquiry, 2) To determine the differences in generic science skills of students who have high critical thinking skills are better than generic science skills students who have low critical thinking skills, 3) To find out the interaction between learning models with the ability to think critically about the generic skills of science of high school students. The type of research used in this study was an experiment. Sampling in this study was carried out by cluster random sampling divided into two classes, namely the first experimental class applied to problem-based learning models and the second experimental class using guided inquiry learning. From the results of this study it can be concluded that the generic science skills of students who use the guided inquiry learning model are better than the problem-based learning model, generic science skills students with high critical thinking skills are better than generic science skills students with low critical thinking skills, and there is no interaction between problem-based learning models and guided inquiry with the ability to think critically towards generic science skills of high school students.